Readiness for self-directed learning among nursing students in Thailand - Areewan Klunklin (2018)
This study took place in Thailand where didactic and lecture-driven teaching styles are beginning to transform into student-centered methods. At Chiang Mai University Faculty of Nursing in Thailand, the readiness of 272 undergraduate students to undertake self-directed learning was investigated using two instruments: a demographic data questionnaire and Guglielmino's Self Directed Learning Readiness Scale. The study found that the overall self-directed learning readiness of participants was at a high level in the categories of openness to learning opportunities, self-concept as an effective learner, initiative and independence in learning, informed acceptance of responsibility for one's own learning, creativity, and the ability to use basic study and problem-solving skills. The findings provide encouragement to nurse educators to further apply self-directed learning in nursing courses, to improve teaching and learning methods, and promote life-long learning for nurses within Thailand and elsewhere. © 2010 Blackwell Publishing Asia Pty Ltd.